Administration of Iranian Propolis attenuates oxidative stress and blood glucose in type II diabetic patients: a randomized, double-blind, placebo-controlled, clinical trial - Sepideh Hesami; Sima Hashemipour; Mohammad reza Shiri-Shahsavar; Yaghob Koushan; Hossein Khadem Haghighian (Babol University of Medical Sciences, 2019)
Background: Hyperglycemia in diabetic people resulted in oxidative conditions. Propolis is the third most important component of bee products which has various functional properties such as anti-oxidant due to its components. The aim of this study was to evaluate the propolis effect on fructosamine level, the catalase activity, and the level of oxidized LDL changes in type 2 diabetic patients. Methods: In this double-blind, randomized controlled trial study, 62 type 2 diabetic patients, attending Endocrine clinic in Velayat Hospital (Qazvin, Iran) in 2017, were randomly assigned to one of intervention and placebo (n=31) groups. Participants in intervention group took propolis capsule (500 mg) 3 times a day and those in placebo group took placebo capsules for 8-week. Fructosamine level, catalase activity and the level of oxidized-LDL were measured at the baseline and at the end of the study. Statistical analysis was performed using SPSS software. Results: At the end of the study, significant differences were seen within groups and in-between groups. In Propolis group compared to the placebo, fructosamine (p<0.05), and the level of oxidized LDL (p<0.05) decreased, and catalase activity (p<0.05) improved. However, there were no significant changes in the placebo group at the end of trial. Conclusion: Eight weeks intake of propolis as a supplement in type II diabetic patients could improve anti-oxidant defense and decline production of hyperglycemia induced products such as fructosamine.